Magnetic attitude control options for earth pointing small satellite - Mohd Suhadis, Nurulasikin (2011)
The active magnetic attitude control technique is a promising attitude control option for small satellites operated in Low Earth Orbit (LEO). It is accomplished using sets of magnetic torquer that can generate a mechanical torque thus producing control actions when the torquers interact with the geomagnetic field. The magnetic attitude control structure can be developed based only on the magnetic torquers or in conjunction with other actuators. The purpose of this thesis is to develop and evaluate the options for the active magnetic attitude control system of low-cost small satellite missions. Three options of control algorithms have been developed for a gravity-gradient satellite and a momentum bias satellite. The first algorithm is structured for the gravity-gradient satellite employing three magnetic torquers onboard (Option A). The algorithm has been configured for controlling roll, pitch and yaw attitudes using a proportional-derivative (PD) controller. The second and the third algorithms are structured for the momentum bias satellite employing three (Option B) and two (Option C) magnetic torquers onboard, respectively. The structured algorithms are for controlling the attitude and nutation of roll/yaw axes using a proportional controller (P) as well as unloading the excess angular momentum of the wheel using a proportional-integral (PI) controller. The developed control algorithms are modeled using the MATLAB SIMULINK codes. The developed control algorithms were tested using the complex and simplified geomagnetic models for a reference space mission. Their attitude performances were compared and it is found that the accuracies of all the three developed control algorithms are comparable and fulfill the mission requirements. However, the system in option B satellite gives a better attitude performance with a perfect pointing accuracy along the pitch axis, whereas between −0.05° and 0.15° along the roll axis and between −0.05° and 0.3° along the yaw axis. This research is dedicated for LEO small satellites in a nominal attitude control operation and it provides us the trade-offs when designing the magnetic attitude control subsystem for low-cost space missions.